Dissolved rare earth element and neodymium isotope distributions in the South China Sea: Water mass source versus particle dissolution - Wu, Qiong; Liu, Zhifei; Colin, Christophe; Douville, Eric; Zhao, Yulong; Wu, Jiawang; Dapoigny, Arnaud; Bordier, Louise; Ma, Pengfei; Huang, Yi (Frontiers in Marine Science, 2022)
Dissolved rare earth elements (REEs) and neodymium isotopes (εNd) have been jointly used to evaluate water mass mixing and lithogenic inputs in the ocean. As the largest marginal sea of the West Pacific, the South China Sea (SCS) is an ideal region for reconstructing past hydrological changes. However, its REE and εNd distributions and underlying controlling mechanisms remain poorly understood. On the basis of four seawater profiles spread across the SCS, this study presents dissolved REE concentrations and εNd data under summer condition to better understand the processes that potentially influence changes in these parameters and their marine cycling. The results show high concentrations of REE and large variations in εNd (‒6.7 to ‒2.8) in surface water, likely caused by the dissolution of riverine and marine particles. Comparison with published data from samples taken during the winter of different years in this and previous studies suggests a possible seasonal variability of middle REE enrichment. The SCS deep water shows a narrow εNd range from ‒4.3 to ‒3.4, confirming the dominant presence of the North Pacific Deep Water in the deep SCS. The intermediate water in the central SCS is characterized by a more negative εNd signal (–4.2 to –3.4) than that found in its counterpart in the West Pacific (–3.5 to –2.8), indicating alterations by deep water through three-dimensional overturning circulation from the northern to southern SCS below ~500 m. The contributions of external sources could be quantitatively estimated for the SCS in terms of Nd. The dissolution of particles from the SCS surrounding rivers (0.26–1.3 tons/yr in summer; 5.6–29 tons/yr in winter) and continental margins (2–12 tons/yr in summer; 23–44 tons/yr in winter) may play an important role in providing additional Nd to the SCS surface water.